FEATURES OF VOCABULARY EXERCISES IN ENGLISH BOOK AT TEN GRADE STUDENTS - Pasaribu, Rosija; Ginting, Elma Gibra Br.; Sirait, Melany Lorenza; Saragih, Erikson (Jurnal Pendidikan Bahasa Inggris undiksha, 2020)
The purpose of this journal analysis is to train the effectiveness of English Foreign Language student practice exercises and vocabulary mastery and reading comprehension. Two specific factors conditions: (a) vocabulary acquisition and retention of different exercises; (b) reading comprehension performance through different exercises. That the results revealed that the qualitative group received significant and superior practice questions and vocabulary mastery the control group who received vocabulary copying exercises on the performance of increasing students' vocabulary, reading comprehension, as well as short-term and long-term word memory retention. Positive correlation between vocabulary knowledge and reading comprehension are also considered. Hence, ignore that vocabulary mastery and question exercises are the more effective types of exercises for vocabulary acquisition and reading understanding.